Worker mobility and productivity spillovers: An emerging market perspective - Ayanda Hlatshwayo; Friedrich Kreuser; Carol Newman; John Rand (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper uses matched employer-employee data from South Africa to examine the extent to which technology transfers between firms through the hiring of workers. Allowing for differential spillovers based on observable technology differences between sending and receiving firms, we find strong evidence for positive productivity spillovers through worker mobility. In contrast to previous studies set in more advanced economies, our results suggest that negative spillovers can occur. Firms that hire workers from less productive firms experience a decline in productivity in the following year compared with similar firms that do not hire any workers. This, we suggest, may be explained by the high skills deficit in the South African labour market, and an important mechanism for technology transfers in the future may be driven by investments in firm-level training initiatives.
Keywords: D24; J24; J62; O33; 330; technology transfers; worker mobility; employer-employee matched data; spillovers